Prophylactic ankle taping: Influence on treadmill-running kinematics and running economy - Paulson, S.; Braun, W. A. (The Journal of Strength and Conditioning Research, 2014)
Prophylactic ankle taping (PAT) is commonly used in sport. Prophylactic ankle taping may restrict ankle motion, which would affect the kinetic chain and alter gait. The purpose of this study was to examine the effects of PAT on lower extremity (LE) kinematics and running economy during treadmill running. Twelve recreational runners (9 women, 3 men; M ± SD age = 31.33 ± 8.04 years, height = 1.67 ± 0.81 m, mass = 61.84 ± 9.38 kg) completed two 20-minute running sessions (PAT and no tape: control [CON]) at a self-selected pace. Before each run, reflective markers were placed along the right side of the body. Sagittal plane kinematic data (60 Hz) were captured 4 times, and expired gases were measured for 2-minute after each video capture during both trials. Stride frequency, stride length, LE kinematic variables at initial contact and end contact (EC) were calculated. Cardiorespiratory variables and heart rate were also measured. Running economy was normalized to oxygen uptake per unit body mass per kilometer (milliliter per kilogram per kilometer) as running speeds varied. At EC, the PAT hip angle significantly decreased (p = 0.01) by 3.82°, whereas CON decreased by 0.85°. The range of motion tended to decrease over the 20-minute run (p = 0.08). Heart rate significantly increased over time (6.7%) but was not different between conditions. Prophylactic ankle taping did not significantly affect the physiological measures associated with the metabolic cost of treadmill running or the other kinematic variables. These findings suggest that the hip angle continued to decrease during the PAT condition at push-off in recreational runners without impacting the metabolic cost of transport.